Shaping Sustainability Reporting Through Managerial Personality: Conceptualizing a Personality-Based Theory of Planned Behavior - Amesh Dulanja Pathirana; Nathasha Kaumadi Shyamanthi (The Indonesian Journal of Accounting Research, 2026)
Despite increasing global emphasis on transparency and sustainability, the adoption of Sustainability Reporting (SR) remains uneven in many emerging nations. Existing research has predominantly focused on institutional and organizational drivers of SR, while the influence of individual managerial characteristics remains comparatively underexplored. Theoretical explanations of managerial characteristics are extremely limited. This conceptual paper proposes a novel theoretical framework to explain managers’ intentions to adopt SR by integrating personality traits into the Theory of Planned Behavior (TPB). Drawing on insights from Upper Echelons Theory (UET) and the Big Five personality framework, the study develops a Personality-based Theory of Planned Behavior (P-TPB) model. The model suggests that personality traits (openness, conscientiousness, extraversion, agreeableness, and neuroticism) shape TPB’s components: attitude, subjective norm, and perceived behavioral control, thereby influencing SR intentions. By incorporating personality traits into the TPB framework, the proposed model extends traditional behavioral explanations and addresses longstanding critiques of TPB for its limited consideration of background psychological factors. The study contributes to the SR literature by shifting the analytical focus from external institutional pressures toward internal managerial drivers. This framework offers an innovative lens on managerial-level drivers of SR. It highlights the significance of personal attributes in shaping corporate behavior. In practice, it informs leadership development, recruitment using personality assessments, and policymaking, particularly in developing economies where individual traits strongly affect organizational practices. The proposed framework provides a foundation for future empirical research on how managerial personality shapes the adoption of SR.